Healthcare delivery for HIV‐positive people with tuberculosis in Europe. Issue 4 (20th November 2020) - Bentzon, AK; Panteleev, A; Mitsura, V; Borodulina, E; Skrahina, A; Denisova, E; Tetradov, S; Podlasin, R; Riekstina, V; Kancauskiene, Z; Paduto, D; Mocroft, A; et al.
Abstract : Background: In a 2013 survey, we reported distinct discrepancies in delivery of tuberculosis (TB) and HIV services in eastern Europe (EE) vs . western Europe (WE). Objectives: To verify the differences in TB and HIV services in EE vs . WE. Methods: Twenty‐three sites completed a survey in 2018 (EE, 14; WE, nine; 88% response rate). Results were compared across as well as within the two regions. When possible, results were compared with the 2013 survey. Results: Delivery of healthcare was significantly less integrated in EE: provision of TB and HIV services at one site (36% in EE vs . 89% in WE; P = 0.034), and continued TB follow‐up in one location (42% vs . 100%; P = 0.007). Although access to TB diagnostics, standard TB and HIV drugs was generally good, fewer sites in EE reported unlimited access to rifabutin/multi‐drug‐resistant TB (MDR‐TB) drugs, HIV integrase inhibitors and opioid substitution therapy (OST). Compared with 2013, routine usage of GeneXpert was more common in EE in 2018 (54% vs . 92%; P = 0.073), as was access to moxifloxacin (46% vs . 91%; P = 0.033), linezolid (31% vs . 64%; P = 0.217), and bedaquiline (0% vs . 25%; P = 0.217). Integration of TB and HIV services (46% vs . 39%; P = 1.000) and provision of OST to patients with opioid dependency (54% vs . 46%; P = 0.695) remained unchanged. Conclusion: Delivery of TB and HIV healthcare, including integration of TB and HIV care and access to MDR‐TB drugs, still differs between WE and EE, as well as between individual EE sites.